Parennialism and Educational Goal - Satin, Sumiani (Journal of Innovation in Teaching and Instructional Media, 2024)
Perennialism argues that values and norms are eternal or everlasting. These values and norms originate from ideas and concepts that have proven to be relevant and beneficial over the years. Perennialism looks back to the past not merely to reminisce about it; instead, they believe that axiomatic principles remain useful in the present time as they are unaffected by time. Perennialist philosophers argue that modern educational practices are crucial because they are based on the customs and cultures of the past, which hold values and ideals still relevant to the firm and just modern life. This article provides information through a review of perennialism in the study of philosophy, encompassing areas such as religious understanding, economics, politics, and education. The writing method employed is article review. The findings indicate that perennialism in religion is motivated by the transcendent unity behind the diversity or plurality of religions and religiosity, according to perennial philosophers. Shared views, or what is referred to as the fundamental message of religion in Islam, demonstrate this transcendent unity: submission to God every day and experiencing His presence in everyday life. The educational goal according to perennialism is to provide knowledge about absolute and eternal truths based on deeply held beliefs, absolute, and timeless.